2021
DOI: 10.1001/jamacardio.2021.2247
|View full text |Cite|
|
Sign up to set email alerts
|

Effect of Paroxetine-Mediated G-Protein Receptor Kinase 2 Inhibition vs Placebo in Patients With Anterior Myocardial Infarction

Abstract: IMPORTANCE Left ventricular remodeling following acute myocardial infarction results in progressive myocardial dysfunction and adversely affects prognosis.OBJECTIVE To investigate the efficacy of paroxetine-mediated G-protein-coupled receptor kinase 2 inhibition to mitigate adverse left ventricular remodeling in patients presenting with acute myocardial infarction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The participants of this study were enrolled in the CARE-AMI trial (clinical trial unique identifier: NCT03274752) ( 8 ). Detailed in- and exclusion criteria have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The participants of this study were enrolled in the CARE-AMI trial (clinical trial unique identifier: NCT03274752) ( 8 ). Detailed in- and exclusion criteria have been reported previously.…”
Section: Methodsmentioning
confidence: 99%
“…Detailed in- and exclusion criteria have been reported previously. In brief, patients presenting with anterior STEMI and reduced LVEF (i.e., ≤ 45%), who underwent primary percutaneous coronary intervention (PCI) within 24 h were eligible for inclusion and underwent baseline CMR after PCI ( 8 ). Exclusion criteria consisted of previous myocardial infarction (MI) or primary percutaneous intervention along with contraindications to CMR ( 8 ) (see Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%
“…In this manuscript, we wanted to investigate why paroxetine could have failed to improve LV remodeling in STEMI patients with LVEF < 45% in a recent trial ( 4 ), despite the very interesting pre-clinical findings studies ( 5 ), attributed to the inhibition of GRK2.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that paroxetine has no beneficial effects on LV remodeling in patients with STEMI and LV ejection fraction ≤ 45%. Specifically, paroxetine treatment was not associated with a recovery in LV ejection fraction compared to placebo ( 4 ). The rationale behind this trial was that paroxetine relieves LV remodeling when administered as a stand-alone medication to mice with MI ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the Original Investigation titled “Effect of Paroxetine-Mediated G-Protein Receptor Kinase 2 Inhibition vs Placebo in Patients With Anterior Myocardial Infarction: A Randomized Clinical Trial,” published online July 14, 2021, in JAMA Cardiology , there were errors in Table 2, Limitations, and the Visual Abstract. In Table 2, Week 18 under Placebo should be Week 12, and the number of participants for that column should be 18.…”
mentioning
confidence: 99%